Interstitial Lung Disease for the Rheumatologist: Pearls and Insights (Canadian Rheumatology Today, 2025)
Interstitial lung disease (ILD) is a potentially life-threatening complication of systemic autoimmune rheumatic diseases (SARDs). Its prevalence varies according to the underlying SARD, being highest in anti-synthetase and anti‑melanoma-differentiation-associated protein 5 (MDA5) syndromes, but affecting the greatest number of individuals in rheumatoid arthritis due to its higher overall frequency.  Because ILD onset may precede, coincide with, or follow SARD diagnosis, rheumatologists may uncover an undiagnosed SARD during ILD evaluation or, conversely, detect ILD through screening of patients with established SARD. The spectrum of SARD-ILD is broad: some patients have mild, stable disease, others experience slowly progressive disease, and some deteriorate rapidly despite treatment, leading to oxygen dependence, lung transplantation, or death. Drug therapies, including immunosuppressive and anti‑fibrotic agents, can slow the progression of SARD-ILD.This article addresses three key clinical questions pertinent to rheumatologists. First, we explore clinical, serological, and morphological features that can aid in diagnosing SARD in patients with ILD, offering practical pearls. Second, we examine screening—covering who to screen, when, how, and at what frequency. Finally, we outline our approach to SARD-ILD management.